Survivors of sexual on women's livelihood narratives on women's livelihood strategies in the Democratic Republic of Congo - DRC prior to the 1996 war - Makhubele, J. C; Zihindula, Bercky M.; Muthuki, Janet (Gender & Behaviour, 2018)
This study explored livelihood strategies that women employed before they were sexual assaulted prior to 1996’s war in DRC. This research was conducted in the South Kivu Province. Qualitative data were collected by means of one-on-one interviews and focus group discussions. Participants were purposelyfully sampled and data was elicited from 55 women. The recorded data were manually transcribed and analysed thematically through the lens of the feminist theory and by means of the gendered livelihood strategies approach. The study revealed that, prior to the 1996 war women had begun to participate economically in their households and this was regarded as one of the ways to overcome the increasing unemployment of men due to the ongoing economic crisis which followed independence, commonly referred to as ‘Zairianization’. Although many women were still totally dependent on men for their livelihood, it was during this period that some women excelled in entrepreneurship.
Article published in the Gender & Behaviour, 16(1), June 2018, 11139 - 11151
Keywords: Women survivors; Livelihood Strategy; Congo; Entrepreneurship; Women’s dependency; Communalism; Postcolonialism; Women in community development; Women in business - Democratic Republic of Congo